PENGARUH BEAUTY INFLUENCER DAN LITERASI HALAL TERHADAP MINAT PEMBELIAN KOSMETIK HALAL DI JAWA TIMUR : Beauty Influencer berpengaruh secara signifikan dan Literasi Halal tidak berpengaruh secara signifikan terhadap minat pembelian kosmetik - Dinda Saira Dewi; Fikriyah Khusnul (Universitas Negeri Surabaya, 2025)
In Indonesia, the most popular activity is online shopping, one of which is shopping for cosmetics. However, many people do not understand the composition of these cosmetics. People tend to buy cosmetics based on price, quality, and real evidence through influencer reviews. Beauty Influencers are a reference for the public, because Beauty Influencers provide information and knowledge about beauty products through social media. However, not all people understand the contents of these cosmetics, so there is a need for knowledge about the guarantee of whether the product is halal or haram through Halal Literacy. Beauty Influencers and Halal Literacy must be a reference for the public in deciding their interest in purchasing cosmetics so that the halal or haram of the goods is guaranteed. With 100 respondents, the purpose of this study was to determine how interest in buying halal cosmetics is influenced by beauty influencers and halal literacy. Using the multiple regression analysis method, data from the questionnaire. This study found that beauty influencers have a significant influence on interest in purchasing halal cosmetics in East Java, while halal literacy does not have a significant influence.